Effect of sertindole on QTc interval in patients with schizophrenia - Atmaca, Murad; Yavuzkir, Mustafa; Mermi, Osman; Topuz, Mehtap; Kanmaz, Ebru; Tezcan, Ertan (Elsevier Ireland Ltd, 2008)
Sertindole has been marketed and offered daily clinical practice only for 9 months in our country, so no data has been its QTc prolongation potential. In the present study, we performed a clinical trial to investigate the effects of sertindole on QTc in patients with schizophrenia. The study comprised 21 patients with schizophrenia. Sertindole was administered in the following dosing regime: treatment was initiated with 4 mg/day sertindole. From day 3 to day 6, the dose was increased to 8 mg/day, and up to day 9, it was raised to 12 mg/day. The protocol allowed up to dose of 20 mg/day according to effectiveness and tolerability. QTc values were determined at beginning, months 3 and 6. In addition, Positive and Negative Syndrome Scale (PANSS) were scored concomitantly. At the beginning of 6-month period, the mean QTc interval of patients was 391.7 +/- 19.2 ms. At the end of this period, it was 402.8 +/- 23.8 ms. Although the mean QTc interval changing was significant throughout 6-month period, of the patients, at any evaluation point, only 1 female (451 ms) and 1 male (433 ms) had borderline prolongation at month 3 for both, without any exceeding the dangerous limits. In summary, our results suggest that sertindole is tolerable and despite dose-related QT prolongation, sertindole had not the proarrhythmic profile. Future studies with larger sample evaluating the effects of treatment are required. (c) 2008 Published by Elsevier Ireland Ltd.
Keywords: QTc; prolongation; sertindole; schizophrenia